Background Values of Soil Heavy Metals in the Huang-Huai-Hai Plain in Henan Province, China - Yuling Jiang; Jianhua Ma; Yuanbo Wang; Yahan Yang (Toxics)
Due to the continuous lack of specific background values (BVs) for soil heavy metals in the Huang-Huai-Hai Plain in Henan province (HPHP), many researchers have used soil heavy BVs specific to Henan Province (HP) or Fluvisols of China (FC) as reference criteria to assess soil heavy metal pollution. However, spatial differences in the soil heavy metal BVs between HPHP, HP, and FC, as well as within the HPHP, remain uncertain, affecting the reliability of evaluation results. A total of 897 surface soil samples were collected from the HPHP, with 336 and 561 samples collected from the southern and northern parts of the Shaying River, respectively. According to the obtained results, the BVs of soil Hg, As, Cd, Cr, Pb, Cu, Zn, and Ni in the HPHP were 0.064, 6.67, 0.129, 53.24, 19.67, 22.87, 64.00, and 26.25 mg·kg−1, respectively. The BVs of soil Hg and Cd were higher than those in HP, Fluvisols in Henan Province, and FC, showing strong and extremely strong levels. The BVs of other soil heavy metals exhibited slight differences from the reference BVs. On the other hand, the BVs of soil Hg, As, Cd, Cr, Pb, Cu, Zn, and Ni were 0.066, 4.11, 0.130, 56.72, 20.97, 23.31, 59.21, and 24.03 mg·kg−1 in the southern part and 0.061, 7.45, 0.129, 51.92, 18.96, 22.72, 66.96, and 27.16 mg·kg−1 in the northern part of the Shaying River, respectively. In addition, there were no significant differences in the Hg and Cd BVs between the two parts. Cu BVs in the southern part were significantly higher than those observed in the northern part, while the As, Zn, and Ni BVs in the northern part were significantly higher than those revealed in the southern part. In contrast, the Cr and Pb BVs in the northern part were significantly lower than those observed in the southern part.